2004
DOI: 10.1073/pnas.0306147101
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of communication between peripheral and central trigeminovascular neurons mediates the antimigraine action of 5HT 1B/1D receptor agonists

Abstract: Triptans are 5HT1B/1D receptor agonists commonly prescribed for migraine headache. Although originally designed to constrict dilated intracranial blood vessels, the mechanism and site of action by which triptans abort the migraine pain remain unknown. We showed recently that sensitization of peripheral and central trigeminovascular neurons plays an important role in the pathophysiology of migraine pain. Here we examined whether the drug sumatriptan can prevent and͞or suppress peripheral and central sensitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
192
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(199 citation statements)
references
References 38 publications
6
192
1
Order By: Relevance
“…Cutaneous allodynia and hyperalgesia develops in the distal extremities during the later stages of migraine headache (Burstein, Cutrer, and Yarnitsky, 2000;Burstein, Collins and Jakubowski, 2004;Levy, Jakubowski and Burstein, 2004;Yarnitsky, Goor-Aryeh, Bajwa, Ransil, Cutre, Sottile and Burstein, 2003). The progression of hyperalgesia from the site of headache to more distal regions implies that sensitization spreads rostally in nociceptive networks as the attack progresses (Burstein et al, 2000).…”
Section: Hyperexcitable Nociception In Migraine Sufferersmentioning
confidence: 99%
“…Cutaneous allodynia and hyperalgesia develops in the distal extremities during the later stages of migraine headache (Burstein, Cutrer, and Yarnitsky, 2000;Burstein, Collins and Jakubowski, 2004;Levy, Jakubowski and Burstein, 2004;Yarnitsky, Goor-Aryeh, Bajwa, Ransil, Cutre, Sottile and Burstein, 2003). The progression of hyperalgesia from the site of headache to more distal regions implies that sensitization spreads rostally in nociceptive networks as the attack progresses (Burstein et al, 2000).…”
Section: Hyperexcitable Nociception In Migraine Sufferersmentioning
confidence: 99%
“…Two studies argue for a significant central, presynaptic mechanism. The first used single unit recordings from both presynaptic trigeminal afferents and postsynaptic neurons with dural receptive fields (Levy et al, 2004). As measured by afferent activity at the trigeminal ganglion, sumatriptan was unable to inhibit peripheral sensitization produced by dural application of inflammatory mediators, but recordings from the second order neurons showed that sumatriptan had, in fact, inhibited the transmission of sensitized afferent activity to the central target.…”
Section: Cns Mechanisms Of Tripan Actionmentioning
confidence: 99%
“…The development of allodynia during migraine appears to be driven by sensitization of trigeminovascular neurons in the dorsal horn which, unfortunately, are not equipped to respond to triptans directly (Potrebic et al, 2003, Levy et al, 2004. Triptans appear to act presynaptically in the dorsal horn, such as to inhibit signal transmission from peripheral (first-order) to central (second-order) trigeminovascular neurons (Levy et al, 2004). Reining-in the central neurons using triptan treatment is possible as long as their excitability remains driven by incoming signals from the meninges, but not after they developed autonomous activity .…”
Section: Introductionmentioning
confidence: 99%